“My Phone is My Baby” - Bittner, Jan-Eric B. (2014)

(untitled)
Due to today’s rapid technological advancements academic research literature on mobile phones from a couple of years ago is already outdated. Therefore, it is necessary to reassess previous literature, which focused on consumption and the importance of mobile phones. The new version of the mobile phone, the smartphone, provides endless opportunities in terms of communication, social interaction and memory creation (taking pictures and videos) for young adults. Being a daily companion it is of interest to explore the deeper meaning of smartphones for young adults. In order to obtain insight on the emotional meaning of smartphones an existential-phenomenological approach with in-depth interviews is used. The outcomes of the study suggest that the smartphone is a crucial possession for young adults that accompanies them through different life stages, helps to relive memories and functions as an extension of the self. Since only a narrow set of international postgraduate and doctorial students from an English University participated, the findings should not be generalized. Nevertheless, the data proposes that the smartphone is a cvital element of a young adults life.